Improve the Ability to Solve Mathematical Problems through Creative Problem-Solving Models - Elisa Dwi Ningrum; Irzal Anderson; Andi Gusmaulia Eka Putri (Journal of Social Science, 2023)
The results showed that there was an increase in the ability to solve mathematical problems in fifth grade students at SDN No. 64/I Muara Bulian through the application of the creative problem-solving model, which is seen in the results of observations of the activities of teachers and students in the first cycle of the first meeting with a percentage of 71,42% learning implementation and the first cycle of the second meeting with a learning implementation percentage of 92.85%. Cycle II meetings I and II got a percentage of 100% implementation of learning. The results of the ability to solve mathematical problems in the first meeting, the percentage of classical completeness was 45,45% the first cycle of the second meeting, the percentage of classical completeness was 59,09%, the second cycle, the fi r st meeting, the percentage of classical completeness was 72,72%, and the second cycle, the second meeting, the percentage classical completeness of 85.71%. Based on the results of the study, it can be concluded that the application of the creative problem-solving model can improve the ability to solve mathematical problems in fifth grade students at SDN No. 64/I Muara Bulian.